A mechanochromic donor-acceptor torsional spring - Maximilian Raisch (Nature Portfolio, 2021)
Force sensing using mechanochromic polymers is currently limited to two state systems and does not allow directly correlating the force with the absorption or emission wavelength. Here, the authors present a mechanochromic donor-acceptor torsional spring that undergoes force-induced planarization during uniaxial elongation leading to force dependent red-shifted absorption and emission spectra.